Kinesin light chain-1 isoform E does not interact with calsyntenin-1. Issue 18 (16th December 2015) - Uchida, Yoko; Gomi, Fujiya
Abstract : β-Amyloid is generated by the sequential cleavage of amyloid precursor protein. Calsyntenin-1 and kinesin light chain-1 splice variant E (KLC1-E) have been proposed to regulate β-amyloid production from amyloid precursor protein. Vesicles containing calsyntenin-1 are transported from the Golgi apparatus to axons by interaction between calsyntenin-1 and KLC1 in their C-terminal regions. However, it is unclear whether KLC1 isoform E influences the interaction between KLC1 and calsyntenin-1, resulting in the impaired axonal transport of calsyntenin-1 vesicles. Here, we show that KLC1-E does not interact with calsyntenin-1 using a pull-down assay, coimmunoprecipitation, and immunocytochemistry. These findings suggest that KLC1-E enrichment may impair the axonal transport of calsyntenin-1 vesicles. Abstract : Supplemental Digital Content is available in the text.